Non-mercury catalytic acetylene hydrochlorination over bimetallic Au–Ba(ii)/AC catalysts. Issue 3 (14th January 2015) - Zhang, Haiyang; Li, Wei; Li, Xueqin; Zhao, Wei; Gu, Junjie; Qi, Xueyan; Dong, Yanzhao; Dai, Bin; Zhang, Jinli
Abstract : Ba(ii ) additives well disperse and inhibit the reduction of Au, and strengthen the reactants adsorption, improving the catalysts' catalytic performance. Abstract : Bimetallic gold–barium catalysts were prepared and assessed for acetylene hydrochlorination, and characterized using low-temperature N2 adsorption/desorption, thermogravimetric analysis, X-ray diffraction, temperature-programmed reduction/desorption, inductively coupled plasma-atomic emission spectroscopy, transmission electron microscopy, and X-ray photoelectron spectroscopy. The best catalytic performance is obtained over Au1Ba(ii )1/AC catalysts with the acetylene conversion of 98.4% and the selectivity to VCM of 99.9%. It is indicated that the addition of Ba(ii ) can make Au species disperse well and inhibit carbon deposition on the catalyst surface; Ba(ii ) additives can enhance the adsorption of reactants on the catalysts but also inhibit the reduction of active gold species during the reaction, consequently augmenting the activity and long-term stability of gold catalysts.